Involvement of NAC083-RbohD module in melatonin-delayed endocarp browning of longan fruit - Shuting Zhang; Jiaqi Xiao; Yueming Jiang (Postharvest Biology and Technology, 2026)

Alpha-ketoglutaric acid alleviates litchi fruit browning and senescence via enhancing antioxidant capacity and energy homeostasis - Yuemin Yang; Rufang Deng; Mengting Liu; Xinguo Su; Yueming Jiang; Xuewu Duan; Guoxiang Jiang; Ting Li (Postharvest Biology and Technology, 2026)

Remote sensing and statistical data integration for spatial discrimination and mapping of mariculture products: A case study of Sansha Bay - Jie Jiang; Xiaomei Yang; Yueming Liu; Zhihua Wang; Guo Yu; Dan Meng; Meiqi Zhou; Jialiang Liu (Ocean & Coastal Management, 2026)

MaHPCA1 alleviates chilling injury in banana fruit - Yu Hou; Peipei Fan; Xiangbin Xu; Zhengke Zhang; Yonggui Pan; Lanhuan Meng; Lisha Zhu; Haiming Chen; Jianbo Xiao; Yueming Jiang; Jiali Yang (Postharvest Biology and Technology, 2026)

Invariant-feature segmentation unlocks robust large-area mapping of mariculture - Ziyu Jiang; Jinyan Xie; Jihao Peng; Huaqing Wu; Yue Liu; Cong Zeng; Yueming Liu; Xiaomei Yang; Ling Cao (Marine Environmental Research, 2026)

Musa acuminata calmodulin-binding transcription activator 4 enhances fruit quality maintenance of banana during cold storage - Ying Li; Youxia Shan; Wanqi Chen; Rufang Deng; Xuewu Duan; Taotao Li; Yueming Jiang (Food Chemistry, 2026)

Efficient identification of allergenic epitopes and analysis of the peptide recognition mechanism in tropomyosin of prawn (penaeus chinensis) through quantum chemistry computational framework - Xiangfei Hu; Qiannan Jiang; Hui Wang; Pingwei Wen; Yueming Hu; Zongcai Tu (Food Chemistry, 2026)

Mechanistic insights into pulsed electric field-induced oxidative degradation of arginine and glutamic acid: Combined experimental characterization and DFT computation - Xiangfei Hu; Qiannan Jiang; Zongcai Tu; Yueming Hu; Hui Wang (Food Research International, 2026)

Arachidonic acid enhances chilling tolerance in banana fruit via coordinated antioxidant system, energy homeostasis and phenylpropanoid metabolism - Youxia Shan; Ying Li; Taotao Li; Wanqi Chen; Xuewu Duan; Yueming Jiang (Food Chemistry, 2026)

Suppressing spectral broadening via intramolecular noncovalent interactions for high-efficiency solution-processed multi-resonance TADF OLEDs - Tao Zhou; Guimin Zhao; Yumiao He; Taiping Chen; Wenwen Tian; Yueming Sun; Wei Jiang (Chemical Engineering Journal, 2026)

BrNAC046 involved in hydrogen peroxide-induced leaf senescence of postharvest Chinese flowering cabbage - Fengjun Li; Baoxiang Ren; Lilang Li; Xiangjin Kong; Hanzhi Liang; Hai Liu; Ling Wang; Yueming Jiang (Postharvest Biology and Technology, 2026)

Itaconate delays senescence and browning in litchi fruit via enhanced antioxidant capacity and energy metabolism - Mengling Qin; Jiaqi Xiao; Yueming Jiang; Xuewu Duan; Mengting Liu; Guoxiang Jiang (Postharvest Biology and Technology, 2026)

Highly amphiphilicity-tailorable pineapple-like janus nanozymes with superior kinematic locomotion facilitates biphasic chemiluminescence analysis - Xin Jiang; Wan Wei; Yueming Zhao; Lingli Zhang; Wenwen Wang; Yuting Zhao; Zhongjie Zhu; Zhifeng Fu; Chengzhou Zhu; Hui Ouyang (Analytica Chimica Acta, 2026)

Host-derived Bacillus velezensis enhances intestinal structure, antioxidant capacity, and pathogen resistance in the American bullfrog (Aquarana catesbeiana) - Yueming Hu; Han Lin; Mengzhen Jiang; Changyi Lin; Hua Li; Jingyang Sun; Kesong Chen; Yebing Yu; Chun Liu (Archives of Microbiology, 2026)

Epigenetic activation of lignin biosynthesis by CsJMJ16 confers enhanced resistance to Penicillium digitatum in citrus - Jing Zeng; Ting Li; Mengting Liu; Xiaoyan Duan; Jiechun Peng; Zhiwei Li; Guoxiang Jiang; Yueming Jiang; Xuewu Duan (Postharvest Biology and Technology, 2026)

Sense, think, and robot control: Multimodal material recognition sensing integrated with large language model reasoning - Zuowei Wang; Fuzheng Zhang; Qijing Lin; Yueming Gao; Bin Sun; Hongze Ke; Na Liu; Bian Tian; Libo Zhao; Zhuangde Jiang (Chemical Engineering Journal, 2026)

Catalase is a critical virulence factor in Aeromonas schubertii infection of snakehead fish (Channa argus) - Mengzhen Jiang; Haiyan Gong; Qing Wang; Han Lin; Yueming Hu; Hua Li; Jingyang Sun; Kesong Chen; Biao Jiang; Wei Li; Youlu Su; Chun Liu (Antonie van Leeuwenhoek, 2026)

Organic matter supply triggers rapid microbial-driven changes in carbon-nitrogen cycling in subterranean estuary sediments - Danqing Sun; Longyun Lai; Yueming Wu; Ying Wu; Jian Li; J. Severino P. Ibánhez; Shan Jiang (Marine Chemistry, 2026)

Meclofenamic acid sodium inhibits litchi fruit senescence via integrated regulation of oxidative stress, energy metabolism, and m6A modification - Mengting Liu; Mengling Qin; Jiaqi Xiao; Yueming Jiang; Xuewu Duan; Guoxiang Jiang (Postharvest Biology and Technology, 2026)

Alpha-ketoglutarate alleviates chilling injury in banana fruit by promoting redox homeostasis and maintaining energy balance - Yuemin Yang; Rufang Deng; Yueming Jiang; Xuewu Duan; Zhengke Zhang; Guoxiang Jiang; Mengting Liu (Postharvest Biology and Technology, 2026)

Effects of glycyrrhizic acid on growth performance and hepato-intestinal health of American bullfrogs (Aquarana catesbeiana) - Zhixiang Bai; Kesong Chen; Xingye Xu; Han Lin; Jingyang Sun; Hua Li; Yueming Hu; Mengzhen Jiang; Wensen Tan; Yanwen Wu; Yebing Yu; Chun Liu (Aquaculture International, 2026)

Distinct mowing effects on organic carbon storage and dynamics in Spartina alterniflora and Phragmites australis sediments - Yueming Wu; Danqing Sun; Shan Jiang; Beiyun Xu; Jing Liu; Jian Li; Yiyun Wang; Ying Wu (Ocean & Coastal Management, 2026)

Pharmacological inhibition of USP7 attenuates deltamethrin-induced neuronal ferroptosis via GPX4 stabilization - Minjia Wu; Yang Chen; Peixuan Ma; Wen Pan; Yaqin Deng; Lexing Wei; Guodong Lu; Michael Aschner; Yueming Jiang; Jing Zhou; Xiaowei Huang (Toxicology and Applied Pharmacology, 2026)

Adenine regulates chilling injury via energy signaling salvage by purine permease MaPUP4 in banana fruit - Youxia Shan; Ying Li; Wanqi Chen; Junxian He; Xuewu Duan; Yueming Jiang (Postharvest Biology and Technology, 2026)

Physicochemical properties of edible oxidized gum arabic–polylysine crosslinked films and their effects on the postharvest preservation of litchi - Dan Li; Huirong Cheng; Ling Xie; Hong Luo; Dandan Zhang; Jupeng Zhao; Yueming Jiang; Liang Gong (Postharvest Biology and Technology, 2026)

Application of riboflavin delays the browning of harvested litchi during storage at room temperature - Jiechun Peng; Ting Li; Mengting Liu; Jiangtao Zhang; Xiaoyan Duan; Ying Li; Hanzhi Liang; Pedro Garcia-Caparros; Yueming Jiang; Xuewu Duan (Food Control, 2026)

Apyrase MaAPY2 regulates the chilling tolerance of banana fruit as a negative modulator - Ying Li; Wanqi Chen; Shule Chen; Zhuojia Mao; Shihan Huang; Rufang Deng; Dandan Zhang; Taotao Li; Xuewu Duan; Yueming Jiang (Postharvest Biology and Technology, 2026)

Mitigating methane emissions from municipal solid waste in Chinese cities - Yueming Gao; Yang Duan; Wei Zhang; Nana Zhao; Yuan Wang; Zhenyu Ding; Wenjun Wu; Dong Cao; Hongqiang Jiang (Journal of Environmental Management, 2026)

Arachidin-2 suppresses Peronophythora litchii and postharvest decay of litchi fruit - Bailin Li; Xueying Meng; Fen Liu; Bao Yang; Sui Kiat Chang; Yueming Jiang (Food Chemistry, 2026)

Dihydromyricetin inhibited DNA methyltransferases activity in citrus fruit to enhance resistance against Penicillium italicum infection - Yanling Ren; Xin Xu; Ying Li; Jianbo Xiao; Yueming Jiang; Taotao Li (Postharvest Biology and Technology, 2025)

Effect of phenolic hydrogen on the formation of chitosan -prenylated flavonoids nanocomplexes - Jinping Wang; Jiawen Chen; Yueming Jiang; Bao Yang; Lingrong Wen (Food Hydrocolloids, 2025)

Activating V4+/V5+ redox couple in polyanion lattice engineered Na3.1V2(PO4)2.9(SiO4)0.1-CNT by synergistic ionotronic strategy - Anyang Yu; Qi Fan; Zilong Fang; Tian Jiang; Xinxin Wang; Xiedie Zhao; Xiaoshuang Ma; Pingping Sun; Gang Li; Shijun Yuan; Haiyang Zhang; Yining Wang; et al. (Chemical Engineering Journal, 2025)

Alveolar macrophages polarization switch via α2-adrenoceptor activation ameliorates pulmonary inflammation following kidney ischemia reperfusion - Jieyu Li; Zhigang Qin; Xinhai He; Ling Jiang; Xiangfeng Liu; Zhengwei Xue; Xiao Li; Yueming Xu; Peng Li; Jianteng Gu (Inflammation Research, 2025)

Modulating immune reactivity of grass carp parvalbumin via pulsed electric field-induced variation of structural properties - Xiangfei Hu; Hui Wang; Qiannan Jiang; Pingwei Wen; Yueming Hu; Zongcai Tu (Food Chemistry, 2025)

New insights of licorice (Glycyrrhiza genus) as a functional food - Lulu Shao; Bailin Li; Yueming Jiang; Bao Yang (Food Chemistry, 2025)

Investigation of the mechanism of H2O2 combined pulsed electric field treatment reducing the antigenicity of parvalbumin and tropomyosin by high-resolution mass spectrometry, molecular dynamics and DFT computation - Xiangfei Hu; Hui Wang; Qiannan Jiang; Pingwei Wen; Jie Cheng; Haibin Liu; Yueming Hu; Zongcai Tu (Innovative Food Science & Emerging Technologies, 2025)

The role of amino acids in delaying the pulp breakdown of litchi fruit during postharvest storage - Lei Wei; Ziming You; Ping Liu; Hong Zhu; Xuewu Duan; Yueming Jiang; Ze Yun (Food Chemistry, 2025)

The role of nano hydrogen water on fruit quality and antioxidant system of dragon fruit during postharvest storage - Ziming You; Lei Wei; Shujing He; Hong Zhu; Xuewu Duan; Yueming Jiang; Ze Yun (Food Chemistry, 2025)

Gene flow network of four major pigments and role of LcmiR2111-KFB14 in pericarp browning of litchi during storage - Jiaqi Xiao; Shuting Zhang; Yijie Zhou; Xiangjin Kong; Hong Zhu; Yueming Jiang; Hongxia Qu (Postharvest Biology and Technology, 2025)

Simulated Study of a Multi-stage Permeable Reactive Barrier for In-Situ AMD Treatment of a Closed High-Sulfur Coal Mine - Yueming Qi; Pei Zhou; Dan Jiang; Lai Zhou; Yanzhuo Liu; Jiehui Zhang (Mine Water and the Environment, 2025)

Hot water treatment enhances mandarin fruit resistance to Penicillium italicum via histone H3K9 and H3K36 methylation modification - Jiechun Peng; Xiaoyan Duan; Hanzhi Liang; Pedro Garcia-Caparros; Yueming Jiang; Xuewu Duan (Postharvest Biology and Technology, 2025)

Frog virus 3: Prevalence survey and quantitative analysis in American bullfrogs using TaqMan MGB probe real-time fluorescence quantitative PCR - Hua Li; Xiaobing Liu; Jingyang Sun; Han Lin; Kesong Chen; Yueming Hu; Mengzhen Jiang; Biao Jiang; Wei Li; Youlu Su; Qing Wang; Chun Liu (Aquaculture, 2025)

MEK1 inhibition ameliorates mitochondrial-dependent apoptosis induced by deltamethrin in mouse hippocampal neuron HT22 cells - Lexing Wei; Yang Chen; Minjia Wu; Peixuan Ma; Huan Wang; Yueming Jiang; Michael Aschner; Jing Zhou; Guodong Lu; Lina Zhao; Xiaowei Huang (Toxicology in Vitro, 2025)

Synergistic impact of plant essential oil based microemulsion on lychee preservation in comparison to Prochloraz - Yujie Shen; Xin Zhou; Jupeng Zhao; Zhe Wang; Dandan Zhang; Lingrong Wen; Yueming Jiang; Liang Gong (Sustainable Chemistry and Pharmacy, 2025)

Epigenetic regulation on fungal disease affecting plant-based food: A review from the perspectives of host, pathogen and their interactions - Yanling Ren; Linyan Feng; Xin Xu; Jianbo Xiao; Yueming Jiang; Taotao Li (Food Bioscience, 2025)

MAPK signaling mediated intestinal inflammation induced by endoplasmic reticulum stress and NOD2 - Siyuan Peng; Yan Zhao; Wang Jiang; Yan Long; Tian Hu; Mengling Li; Jinyue Hu; Yueming Shen (Molecular and Cellular Biochemistry, 2025)

Tyr-Asp treatment delays senescence in litchi fruit by enhancing redox balance and maintaining energy homeostasis - Ruan Zhiyan; Yanxuan Zhu; Mengting Liu; Yijie Zhou; Xinguo Su; Yueming Jiang; Guoxiang Jiang (Postharvest Biology and Technology, 2025)

Corrigendum to ''Tyr-Asp enhances chilling tolerance in banana fruit by modulating redox homeostasis'' [Postharvest Biol. Technol., vol., 222, April 2025, 113338] - Yanxuan Zhu; Yiejie Zhou; Zhiwei Li; Ruimin Zhong; Yueming Jiang; Guoxiang Jiang; Xinguo Su (Postharvest Biology and Technology, 2025)

Transcription factor AcAGL9 and AcBEH1 synergistically regulate carotenoid biosynthesis during pineapple fruit ripening - Mengting Liu; Ting Li; Rufang Deng; Zhengke Zhang; Yijie Zhou; Xuewu Duan; Yueming Jiang; Guoxiang Jiang (Postharvest Biology and Technology, 2025)

Tyr-Asp enhances chilling tolerance in banana fruit by modulating redox homeostasis - Yanxuan Zhu; Yiejie Zhou; Zhiwei Li; Ruimin Zhong; Yueming Jiang; Guoxiang Jiang; Xinguo Su (Postharvest Biology and Technology, 2025)

Purification and identification of antioxidant activity and angiotensin converting enzyme (ACE) inhibitory activity peptide of peanut protein based on ultrafiltration (UF) membrane separation - Bin Cao; Qi Li; Zhenyu Chen; Xiuren Tang; Hock Eng Khoo; Tiemin Jiang; Yueming Jiang; Jing Li; Xinhong Dong (Food Bioscience, 2025)

New insights of flavonoid glycosidases and their application in food industry - Yingjun Liu; Qiuxia Yang; Yushan Guo; Yueming Jiang; Hong Zhu; Bao Yang (Critical Reviews in Food Science and Nutrition, 2025)

The effect of resveratrol on lead-induced oxidative damage and apoptosis in HT-22 cells - Xiang Yi; Ruokun Wei; Shaoni Huang; Peiqi Wei; HuiShuai Li; Zhenning Li; Michael Aschner; Yueming Jiang; Shiyan Ou; Shaojun Li (Food and Chemical Toxicology, 2025)

Mechanism studies of gliadin-glucose glycation reaction and products formation by heat treatment with different conduction modes - Qiannan Jiang; Xiangfei Hu; Zongcai Tu; Pingwei Wen; Yueming Hu; Siqiong Zhang; Hui Wang; Zuohua Xie (Food Chemistry, 2025)

Exploring the influence of extruded rice adjunct on wort separation efficiency: A bio-macromolecule degradation perspective - Lijun Jiang; Jialin Song; Mingming Qi; Feng Han; Mei Xu; Yueming Li; Dongliang Zhang; Shifeng Yu; Hongjun Li (Food Chemistry, 2025)

Arabinogalacturonan in functional food “Astragalus membranaceus root”: Structure and immunomodulatory activity - Zhili Sheng; Hui Liu; Bailin Li; Hong Zhu; Yueming Jiang; Bao Yang (Food Hydrocolloids, 2025)

Higher dynamic and turnover yet enhanced organic carbon burial in Spartina alterniflora sediments: A case study in a temperate coastal wetland - Yueming Wu; Beiyun Xu; Danqing Sun; Shan Jiang; Jian Li; Yiyun Wang; Ying Wu (CATENA, 2025)

Phytosulfokine treatment delays browning of litchi pericarps during storage at room temperature - Hanzhi Liang; Yanxuan Zhu; Zhiwei Li; Yueming Jiang; Xuewu Duan; Guoxiang Jiang (Postharvest Biology and Technology, 2025)

Gallic acid reduces pericarp browning of litchi fruit during storage - Chunlan Wang; Shuting Zhang; Dandan Zhang; Fengjun Li; Lihong Xie; Tingrui Dai; Yueming Jiang (Postharvest Biology and Technology, 2025)

Improving the functional components and biological activities of navel orange juice through fermentation with an autochthonous strain Lactiplantibacillus paraplantarum M23 - Meiling Huang; Chunling Lai; Yan Liang; Qin Xiong; Chaoyun Chen; Zhiran Ju; Yueming Jiang; Jun Zhang (Food and Bioproducts Processing, 2025)

Association between exposure to arsenic, cadmium, and lead and chronic kidney disease: evidence from four practical statistical models - Jiongli Huang; Jingying Mao; Huilin Liu; Zhongyou Li; Guiyun Liang; Dabiao Zhang; Junchao Yang; Wen Qin; Pingjing Wen; Yueming Jiang; Zhaoyu Mo (Environmental Geochemistry and Health, 2025)

An update of aurones: food resource, health benefit, biosynthesis and application - Jiali Yang; Zhengjiao Gao; Zhiqian Yu; Yu Hou; Dingtao Tang; Huiling Yan; Fuwang Wu; Sui Kiat Chang; Yonggui Pan; Yueming Jiang; Zhengke Zhang; Bao Yang (Critical Reviews in Food Science and Nutrition, 2024)

Functional analysis of LcDORN1 genes in the senescence of litchi fruit - Yijie Zhou; Zhiwei Li; Xiangjin Kong; Jiaqi Xiao; Yueming Jiang; Xinguo Su; Hongxia Qu (Postharvest Biology and Technology, 2024)

Fermentation by Penicillium polonicum improves the functional components and biological effects of orange peel via producing β-glucosidase without the risk of potential mycotoxins - Yan Liang; Chunling Lai; Liangliang Gao; Qingna Wu; Meiling Huang; Yueming Jiang; Jun Zhang (Food Bioscience, 2024)

Citrus exosome-modified exogenous dsRNA delivery reduces plant pathogen resistance and mycotoxin production - Chunxiao Yin; Yuli Lao; Lihong Xie; Lianfei Chen; Yueming Jiang; Liang Gong (Pesticide Biochemistry and Physiology, 2024)

Fabrication of antimicrobial packaging based on polyaminopropyl biguanide incorporated pectin/polyvinyl alcohol films for fruit preservation - Mingyang He; Jinpeng Pan; Min Hong; Yujie Shen; Heng Zhang; Yueming Jiang; Liang Gong (Food Chemistry, 2024)

Tert-Butylhydroquinone retards longan fruit deterioration by regulating membrane lipid and energy metabolisms - Zhiqian Yu; Dingtao Tang; Zhengke Zhang; Yueming Jiang; Jiali Yang; Yonggui Pan (Food Chemistry, 2024)

Vitexin is a potential postharvest treatment for ameliorating litchi fruit pericarp browning by regulating autophagy - Qiuxiao Yang; Dingding Shi; Yanling Ren; Chao Yang; Hongxia Qu; Yueming Jiang; Taotao Li (Postharvest Biology and Technology, 2024)

Advances in gas fumigation technologies for postharvest fruit preservation - Wanli Zhang; Yonggui Pan; Yueming Jiang; Zhengke Zhang (Critical Reviews in Food Science and Nutrition, 2024)

The role of hydrogen-rich water in delaying the pulp breakdown of litchi fruit during postharvest storage - Huijun Gao; Feiyan Li; Xi Chen; Ziming You; Lei Wei; Yuanlong Liu; Ping Liu; Mingyang He; Min Hong; Hong Zhu; Xuewu Duan; Yueming Jiang; et al. (Food Chemistry, 2024)

Hydrogen peroxide receptors regulate chilling injury of banana fruit during low-temperature storage - Shuting Zhang; Youxia Shan; Ying Li; Junxian He; Yueming Jiang (Postharvest Biology and Technology, 2024)

Lead exposure induces neurodysfunction through caspase-1-mediated neuronal pyroptosis - Dongjie Peng; Leilei Wang; Yuanyuan Fang; Lili Lu; Zhaocong Li; Siyang Jiang; Jing Chen; Michael Aschner; Shaojun Li; Yueming Jiang (Environmental Research, 2024)

Pore shrinkage capacity of Shajiang black soils (Vertisols) on the North China Plain and its influencing factors - Yueming CHEN; Zhongbin ZHANG; Lei GAO; Zichun GUO; Peng XIONG; Fahui JIANG; Xinhua PENG (Pedosphere, 2024)

The structure characteristics, biosynthesis and health benefits of naturally occurring rare flavonoids - Shengtao Bo; Sui Kiat Chang; Yipeng Chen; Zhili Sheng; Yueming Jiang; Bao Yang (Critical Reviews in Food Science and Nutrition, 2024)

Green and efficient approach to extract bioactive flavonoids with antioxidant, antibacterial, antiglycation, and enzyme inhibitory activities from navel orange peel - Chunling Lai; Meiling Huang; Qin Xiong; Yan Liang; Yueming Jiang; Jun Zhang (Sustainable Chemistry and Pharmacy, 2024)

Identification of groundwater pollution sources and health risk assessment in the Fengshui mining area of Central Shandong, China - Hongyu Li; Jiaxin Wu; Yueming Qi; Chengzhi Su; Dan Jiang; Pei Zhou (Environmental Science and Pollution Research, 2024)

Involvement of LcmiR482e-LcACA2 mediated energy metabolism in senescence of harvested litchi fruit - Jiaqi Xiao; Yunyun Xie; Xiangjin Kong; Kuan Peng; Hong Zhu; Yueming Jiang; Hongxia Qu (Postharvest Biology and Technology, 2024)

Water quality and microecosystem of water tanks in karst mountainous area, Southwest China - Qigang Wang; Guanghui Jiang; Ziyong Sun; Yueming Liang; Fan Liu; Jie Shi (Environmental Science and Pollution Research, 2024)

Control of citrus blue and green molds by Actinomycin X2 and its possible antifungal mechanism - Liangliang Gao; Yan Liang; Qin Xiong; Meiling Huang; Yueming Jiang; Jun Zhang (Pesticide Biochemistry and Physiology, 2024)

Understanding the degradation mechanisms of cyanide and starch in cassava flour during extrusion processing - Mingming Qi; Jialin Song; Lijun Jiang; Luxia Li; Mei Xu; Yueming Li; Shifeng Yu; Hongjun Li (Innovative Food Science & Emerging Technologies, 2024)

Identification and stability evaluation of polyphenol oxidase substrates of pineapple fruit - Hai Liu; Jiangming Li; Yueming Jiang; Fengjun Li (Food Chemistry, 2024)

Fe mediated alleviation effect of cadmium toxicity in mangrove Avicennia marina (Forssk.) Vierh - Jian Li; Yueming Wu; Xiaotong Guo; Shan Jiang; Zhanrui Leng; Jiaojiao Xia; Chongyu Zhuo; Hui Jia; Daolin Du (Frontiers in Marine Science, 2023)
Iron (Fe) supply is one of the key factors in alleviating cadmium (Cd) stress in different plants, including mangroves. However, the effects and mechanisms of Fe in mediating the mangrove response to Cd stress still need to elaborate on the level of plant physiology and metabolism. Herein a 40-day hydroponic study was conducted to evaluate the mediating effect of Fe on Cd tolerance of Avicennia marina (Forssk.) Vierh. Results showed that the Fe supply directly improved the activity of ferric chelate reductase (FCR), increased Fe concentration in tissues, enhanced its competitiveness with Cd, and improved Fe bioavailability, thereby reducing the uptake of Cd by plants. Simultaneously, moderate Fe enhanced the photosynthesis and increased concentrations of total phenolics and tannins in both roots and leaves that play a critical role in chelating and immobilizing Cd, thus restricting the Cd translocation from roots to aboveground tissues. Additionally, the application of Fe significantly upregulated the activity of antioxidant enzymes, including POD and PPO and hence scavenging the reactive oxygen species caused by Cd stress. In conclusion, moderate Fe application improved the growth of A. marina and enhanced its tolerance to Cd at physiological and metabolic levels. Therefore, improving Fe bioavailability will reduce the mangrove degradation caused by Cd contamination, and also this may be a potential way to restore contaminated mangrove ecosystems. Protecting and restoring mangroves is not only essential for preserving biodiversity and supporting coastal ecosystems but also crucial for maintaining their role as crucial carbon sinks (i.e., mangrove blue carbon) combating global warming and climate change.

Coupling strength between omnivory loops and their one-species-delete subloops drives real food web stability - Jianfeng Feng; Shengpeng Li; Xiaoxiao Li; Yueming Jiang; Ruyue Wang; Xianhao Meng; Wei Yang; Tao Sun; Peter C. de Ruiter; Yongtang Shi; Nils Chr. Stenseth (Theoretical Ecology, 2023)

Ubiquitin ligase enzymes and de-ubiquitinating enzymes regulate innate immunity in the TLR, NLR, RLR, and cGAS-STING pathways - Wang Jiang; Mengling Li; Siyuan Peng; Tian Hu; Yan Long; Jiayi Zhang; Dan Peng; Yueming Shen (Immunologic Research, 2023)

Increased aerosol scattering contributes to the recent monsoon rainfall decrease over the Gangetic Plain - Tong Ying; Jing Li; Zhongjing Jiang; Guanyu Liu; Zhenyu Zhang; Lu Zhang; Yueming Dong; Chuanfeng Zhao (Science Bulletin, 2023)

Effects of different high-temperature conduction modes on the ovalbumin-glucose model: AGEs production and regulation of glycated ovalbumin on gut microbiota - Haiqi Chen; Yanru Zhou; Siqiong Zhang; Zuohua Xie; Pingwei Wen; Hui Wang; Yueming Hu; Peihan Wu; Jiaojiao Liu; Qiannan Jiang; Zongcai Tu (Food Research International, 2023)

Comparison of ovalbumin glycation induced by high-temperature steaming and high-temperature baking: A study combining conventional spectroscopy with high-resolution mass spectrometry - Yueming Hu; Haiqi Chen; Yifan Yang; Siqiong Zhang; Zuohua Xie; Jiaojiao Liu; Qiannan Jiang; Jun Liu; Pingwei Wen (Food Research International, 2023)

Interaction between ultrasound-modified pectin and icaritin - Yipeng Chen; Yueming Jiang; Lingrong Wen; Bao Yang (Food Chemistry, 2023)

Naturally occurring prenylated stilbenoids: food sources, biosynthesis, applications and health benefits - Shengtao Bo; Sui Kiat Chang; Hong Zhu; Yueming Jiang; Bao Yang (Critical Reviews in Food Science and Nutrition, 2023)

New insights of fig (Ficus carica L.) as a potential function food - Qiuxia Yang; Yingjun Liu; Yushan Guo; Yueming Jiang; Lingrong Wen; Bao Yang (Trends in Food Science & Technology, 2023)

Relationship between summer time near-surface ozone concentration and planetary boundary layer height in Beijing - Chongzhao Zhang; Zhongjing Jiang; Meijing Liu; Yueming Dong; Jing Li (Atmospheric Research, 2023)

Retrieval of aerosol single scattering albedo using joint satellite and surface visibility measurements - Yueming Dong; Jing Li; Xing Yan; Chong Li; Zhongjing Jiang; Changrui Xiong; Liang Chang; Lu Zhang; Tong Ying; Zhenyu Zhang (Remote Sensing of Environment, 2023)

Unveiling metabolome heterogeneity and new chemicals in 7 tomato varieties via multiplex approach of UHPLC-MS/MS, GC–MS, and UV–Vis in relation to antioxidant effects as analyzed using molecular networking and chemometrics - Asmaa M. Otify; Rana M. Ibrahim; Bishoy Abib; Annegret Laub; Ludger A. Wessjohann; Yueming Jiang; Mohamed A. Farag (Food Chemistry, 2023)

Microbiota of a seepage face at the mouth of a subterranean estuary: diversity, distribution and substrate dependence - Yueming Wu; Yongjun Wei; Juan Severino Pino Ibánhez; Danqing Sun; Kaiqi Lu; Qianqian Wang; Jian Li; Shan Jiang (Acta Oceanologica Sinica, 2023)

A viologen-based conductive hydrogel enables iontophoresis devices powered by Mg biobattery - Yan Zhou; Shan Jiang; Xuenan Ma; Yueming Mu; Jiaxin Zhao; Qin Liang; Xiaoteng Jia; Danming Chao (Chemical Engineering Journal, 2023)

The roles of exogenous ATP in postharvest fruit and vegetable: A systematic meta-analysis - Youxia Shan; Shuting Zhang; Ying Li; Jun Zhang; Mohamed A. Farag; Jun-Xian He; Jianbo Xiao; Hongxia Qu; Xuewu Duan; Yueming Jiang (Postharvest Biology and Technology, 2023)

Linoleic acid from the endophytic fungus Diaporthe sp. HT-79 inhibits the growth of Xanthomonas citri subsp. citri by destructing the cell membrane and producing reactive oxygen species (ROS) - Huiting Lin; Yan Liang; Kumaravel Kaliaperumal; Qin Xiong; Shuo Duan; Yueming Jiang; Jun Zhang (Pesticide Biochemistry and Physiology, 2023)

Structure identification of the oligosaccharides by UPLC-MS/MS - Qiuxia Yang; Yushan Guo; Yueming Jiang; Bao Yang (Food Hydrocolloids, 2023)

Amelioration of chilling injury in ‘Guifei’ mango fruit by melatonin is associated with regulation of lipid metabolic enzymes and remodeling of lipidome - Ping Xu; Donald J. Huber; Di Gong; Ze Yun; Yonggui Pan; Yueming Jiang; Zhengke Zhang (Postharvest Biology and Technology, 2023)

MaMYB13 is involved in response to chilling stress via activating expression of VLCFAs and phenylpropanoids biosynthesis-related genes in postharvest banana fruit - Zhiwei Li; Yijie Zhou; Hanzhi Liang; Qing Li; Yueming Jiang; Xuewu Duan; Guoxiang Jiang (Food Chemistry, 2023)

A NAC transcriptional factor BrNAC029 is involved in cytokinin-delayed leaf senescence in postharvest Chinese flowering cabbage - Fengjun Li; Youxia Shan; Haobin Wang; Guoxiang Jiang; Xiaochun Ding; Hanzhi Liang; Chunlan Wang; Xiangjin Kong; Lihong Xie; Yueming Jiang (Food Chemistry, 2023)

Involvement of miRNAs-mediated senescence and salicylic acid defense in postharvest litchi downy blight - Chunxiao Yin; Lihong Xie; Yanfei Wu; Hongxia Qu; Bao Yang; Liang Gong; Yueming Jiang; Taotao Li (Food Chemistry, 2023)

Nitric oxide is involved in melatonin-induced cold tolerance in postharvest litchi fruit - Jialiang Liu; Wanli Zhang; Meijiao Hu; Yonggui Pan; Yueming Jiang; Zhengke Zhang; Guoxiang Jiang (Postharvest Biology and Technology, 2023)

Multiple metabolomics comparatively investigated the pulp breakdown of four dragon fruit cultivars during postharvest storage - Qixian Wu; Huijun Gao; Ziming You; Zhengke Zhang; Hong Zhu; Mingyang He; Junxian He; Xuewu Duan; Yueming Jiang; Ze Yun (Food Research International, 2023)

Degradation of water-soluble polysaccharides in pulp of litchi during storage - Zhongsuzhi Chen; Meiying He; Yijie Zhou; Xi Chen; Hong Zhu; Bao Yang; Yueming Jiang; Hongxia Qu (Food Chemistry, 2023)

Correction to: Effects of Sub-chronic Lead Exposure on Essential Element Levels in Mice - Shaojun Li; Chun Yang; Xiang Yi; Ruokun Wei; Michael Aschner; Yueming Jiang; Shiyan Ou; Chaocong Yao (Biological Trace Element Research, 2023)

Effects of Sub-chronic Lead Exposure on Essential Element Levels in Mice - Shaojun Li; Chun Yang; Xiang Yi; Ruokun Wei; Michael Aschner; Yueming Jiang; Shiyan Ou; Chaocong Yao (Biological Trace Element Research, 2023)

DEM-CFD investigation on the effects of angularity and roughness on the mass loss of soil rock mixtures - Fan Chen; Yingchao Wang; Wen Jiang; Yin Guo; Yueming Wang (European Journal of Environmental and Civil Engineering, 2022)

Prenylated flavonoids in foods and their applications on cancer prevention - Lingrong Wen; Ting Zhou; Yueming Jiang; Sui Kiat Chang; Bao Yang (Critical Reviews in Food Science and Nutrition, 2022)

The IAMAS-CNC Early Career Scientists Nobel Prize Online Interpretation Workshop - Jing Li; Zhongjing Jiang; Yueming Dong; Lu Zhang; Tong Ying; Zhenyu Zhang; Mu Mu (Advances in Atmospheric Sciences, 2022)

Seasonal Variation of Food Web Structure and Stability of a Typical Artificial Reef Ecosystem in Bohai Sea, China - Shengpeng Li; Ruyue Wang; Yueming Jiang; Yanyu Li; Lin Zhu; Jianfeng Feng (Frontiers in Marine Science, 2022)
The last 30 years have witnessed the degradation and loss of function in the ecosystem of the Bohai Sea, China. Great efforts, such as artificial reefs, have been used to restore the ecosystem of the Bohai Sea in recent years. In this study, we examined the seasonal variation of food webs in artificial reefs of Juehua Island by the Ecopath model. Results showed that the number of species, range of trophic level, energy cycle proportion, energy complexity, nutrition transfer efficiency, and ecosystem maturity have increased from summer to autumn. However, the food web stability of artificial reefs has no obvious change from summer to autumn. Loop analysis revealed that the heaviest feedback loops are the interactions among benthos, zooplankton, and phytoplankton, and the predator-prey negative interaction strength between zooplankton and phytoplankton dominated the stability of the artificial reef, whether in summer or autumn. This study suggests that stability is a more robust indicator for ecosystem assessment and could provide useful information in future restoration plans of the marine ecosystem.

Sodium P-aminosalicylic Acid Attenuates Manganese-Induced Neuroinflammation in BV2 Microglia by Modulating NF-κB Pathway - Junyan Li; Yue Deng; Dongjie Peng; Lin Zhao; Yuanyuan Fang; Xiaojuan Zhu; Shaojun Li; Michael Aschner; Shiyan Ou; Yueming Jiang (Biological Trace Element Research, 2021)

Protective Effects of Sodium Para-aminosalicylic Acid on Manganese-Induced Damage in Rat Pancreas - Xiaojuan Zhu; Bingyan Xie; Dianyin Liang; Wenxia Qin; Lin Zhao; Yue Deng; Pingjing Wen; Fang Xu; Michael Aschner; Yueming Jiang; Shiyan Ou (Biological Trace Element Research, 2021)

Sodium P-aminosalicylic Acid Inhibits Manganese-Induced Neuroinflammation in BV2 Microglial Cells via NLRP3-CASP1 Inflammasome Pathway - Yuanyuan Fang; Dongjie Peng; Yuan Liang; Lili Lu; Junyan Li; Lin Zhao; Shiyan Ou; Shaojun Li; Michael Aschner; Yueming Jiang (Biological Trace Element Research, 2021)

Effect of aluminate content in cement on the long-term sulfate resistance of cement stabilized sand - Kaiwei Liu; Yueming Wang; Ning-Jun Jiang; Aiguo Wang; Daosheng Sun; Xingxing Chen (Marine Georesources & Geotechnology, 2020)

Interaction between serine carboxypeptidase-like protein TtGS5 and Annexin D1 in developing seeds of Triticum timopheevi - Peihong Jiang; JianSheng Gao; Junyi Mu; Luning Duan; Yunsong Gu; Shichen Han; Lin Chen; Yaxuan Li; Yueming Yan; Xiaohui Li (Journal of Applied Genetics, 2020)

Analyzing the action of evolutionarily conserved modules on HMW-GS 1Ax1 promoter activity - Luning Duan; Shichen Han; Ke Wang; Peihong Jiang; Yunsong Gu; Lin Chen; Junyi Mu; Xingguo Ye; Yaxuan Li; Yueming Yan; Xiaohui Li (Plant Molecular Biology, 2020)

Proteomic and transcriptomic analysis to unravel the influence of high temperature on banana fruit during postharvest storage - Taotao Li; Qixian Wu; Xuewu Duan; Ze Yun; Yueming Jiang (Functional & Integrative Genomics, 2019)

Long-term exposure to low level of fluoride induces apoptosis via p53 pathway in lymphocytes of aluminum smelter workers - Pingjing Wen; Xiaomin Wei; Guiqiang Liang; Yanfei Wang; Yiping Yang; Lilin Qin; Weiyi Pang; Guangqiu Qin; Hai Li; Yueming Jiang; Qijun Wu (Environmental Science and Pollution Research, 2019)

Reservoir characteristics and main controlling factors of the Longwangmiao Formation in the Moxi area, central Sichuan Basin, China - Xuefei Yang; Xingzhi Wang; Hao Tang; Yueming Yang; Jirong Xie; Wenjun Luo; Nan Jiang (Arabian Journal of Geosciences, 2016)

Water loss from litchi (Litchi chinensis) and longan (Dimocarpus longan) fruits is biphasic and controlled by a complex pericarpal transpiration barrier - Markus Riederer; Katja Arand; Markus Burghardt; Hua Huang; Michael Riedel; Ann-Christin Schuster; Anna Smirnova; Yueming Jiang (Planta, 2015)

Natural Occurrence, Analysis, and Prevention of Mycotoxins in Fruits and their Processed Products - Jinyi Yang; Jing Li; Yueming Jiang; Xuewu Duan; Hongxia Qu; Bao Yang; Feng Chen; Dharini Sivakumar (Critical Reviews in Food Science and Nutrition, 2014)

Effect of hydroxyl radical on the scission of cellular wall polysaccharides in vitro of banana fruit at various ripening stages - Guiping Cheng; Xuewu Duan; Bao Yang; Yueming Jiang; Wangjin Lu; Yunbo Luo; Weibo Jiang (Acta Physiologiae Plantarum, 2008)

Characterization of seed hordeins and varietal identification in three barley species by high-performance capillary electrophoresis - Yueming Yan; Yi Jiang; Jianzhong Yu; Minhua Cai; Yingkao Hu; Dragan Perovic (Cereal Research Communications, 2003)

Allelic variation of the HMW glutenin subunits in Aegilops tauschii accessions detected by sodium dodecyl sulphate (SDS-PAGE), acid polyacrylamide gel (A-PAGE) and capillary electrophoresis - Yueming Yan; S.L.K. Hsam; Jianzhong Yu; Yi Jiang; F.J. Zeller (Euphytica, 2003)

Effect of Abscisic Acid on Banana Fruit Ripening in Relation to the Role of Ethylene - Yueming Jiang; Daryl C. Joyce; Andrew J. Macnish (Journal of Plant Growth Regulation, 2000)